Preservation of muscle mass as a strategy to reduce the toxic effects of cancer chemotherapy on body composition - Pin, Fabrizio; Couch, Marion E; Bonetto, Andrea (Current opinion in supportive & palliative care, 2018)
Cancer patients undergoing chemotherapy often experience very debilitating side effects, including unintentional weight loss, nausea, and vomiting. Changes in body composition, specifically lean body mass (LBM), are known to have important implications for anticancer drug toxicity and cancer prognosis. Currently, chemotherapy dosing is based on calculation of body surface area, although this approximation does not take into consideration the variability in lean and adipose tissue mass. Patients with depletion of muscle mass present higher chemotherapy-related toxicity, whereas patients with larger amounts of LBM show fewer toxicities and better outcomes. Commonly used chemotherapy regimens promote changes in body composition, primarily by affecting skeletal muscle, as well as fat and bone mass. Experimental evidence has shown that pro-atrophy mechanisms, abnormal mitochondrial metabolism, and reduced protein anabolism are primarily implicated in muscle depletion. Muscle-targeted pro-anabolic strategies have proven successful in preserving lean tissue in the occurrence of cancer or following chemotherapy. Muscle wasting often occurs as a consequence of anticancer treatments and is indicative of worse outcomes and poor quality of life in cancer patients. Accurate assessment of body composition and preservation of muscle mass may reduce chemotherapy toxicity and improve the overall survival.